Determinants of inter-practice variation in childhood asthma and respiratory infections: cross-sectional study of a national sentinel network. Issue 1 (24th January 2019) - Hoang, Uy; Liyanage, Harshana; Coyle, Rachel; Godden, Charles; Jones, Simon; Blair, Mitch; Rigby, Michael; de Lusignan, Simon
Abstract : Objectives: Respiratory infections are associated with acute exacerbations of asthma and accompanying morbidity and mortality. In this study we explore inter-practice variations in respiratory infections in children with asthma and study the effect of practice-level factors on these variations. Design: Cross-sectional study. Setting: We analysed data from 164 general practices in the Royal College of General PractitionersResearch and Surveillance Centresentinel network in England. Participants: Children 5–12 years. Interventions: None. In this observational study, we used regression analysis to explore the impact of practice-level determinants on the number of respiratory infections in children with asthma. Primary and secondary outcome measures: We describe the distribution of childhood asthma and the determinants of upper/lower respiratory tract infections in these children. Results: 83.5% (137/164) practices were in urban locations; the mean number of general practitioners per practice was 7; and the mean duration since qualification 19.7 years. We found almost 10-fold difference in the rate of asthma (1.5–11.8 per 100 children) and 50-fold variation in respiratory infection rates between practices. Larger practices with larger lists of asthmatic children had greater rates of respiratory infections among these children. Conclusion: We showed that structural/environmental variables are consistent predictors of a range of respiratory infections among children with asthma. However, contradictory results between measures of practice clinical care show that a purely structural explanation for variability in respiratory infections is limited. Further research is needed to understand how the practice factors influence individual risk behaviours relevant to respiratory infections.